A case of inappropriate implantable cardioverter defibrillator therapy induced by T‐wave oversensing due to hyperkalemia. Issue 6 (9th June 2015) - Aoki, Kosuke; Okajima, Katsunori; Kiuchi, Kunihiko; Yokoi, Kiminobu; Teranishi, Jin; Shimane, Akira
Abstract: There have been reports of hyperkalemia‐induced T‐wave oversensing in patients with implantable cardioverter defibrillators (ICDs). However, a comparison of T‐wave amplitudes and morphologies between the surface 12‐lead electrocardiogram (ECG) and ICD electrogram has not been reported. We present the case of a 70‐year‐old man who received inappropriate ICD shocks due to hyperkalemia‐induced T‐wave oversensing. The T‐wave amplitudes on both the ICD electrogram and 12‐lead ECG corresponded and normalized after normalization of the potassium level.